الأدوات والآلات الموسيقية الشعبية من متطلبات الحياة الترفيهية الفلسطينية ودورها في تجسيد الهوية الوطنية آلة موسيقية شعبية نسيها الزمن الربابة ذات الوتر الحزين من الأدوات الموسيقية الشعبية ودورها في إثراء المشهد الفني في فلسطين أنموذجا - جرادات, ادريس (roa, 2020)
سعت الدراسة إلى تحقيق ما يأتي: 1-العمل على إحياء جانب مهم من التراث الفلسطيني، وهو الأدوات الموسيقية الشعبية، والحرف التقليدية لتنميتها ،والمحافظة عليها. 2-إبراز البعدين التراثي والحضاري للصناعات الشعبية التي تعبر عن تاريخ الشعب الفلسطيني وثقافته ، حيث تجسد الوجود الفلسطيني على أرضه. 3- الأدوات الموسيقية الشعبية هي صديقة البيئة .        اتبعت الدراسة المنهج الوصفي الذي يسير وفق الخطوات الآتية:الجانب الوصفي لواقع الأدوات الموسيقية الشعبية-الربابة ذات الوتر الحزين- ،والمنهج المكتبي بالرجوع إلى الكتب والمجلات وما كتب عن الصناعات المنقرضة خاصة.          استخدمت الدراسة الملاحظة المقصودة المباشرة، وذلك لتجميع الخبرات حول ما نشاهده، أو  نسمع عنه، أو نعايشه، وذلك للتعرف إلى واقع الأدوات الموسيقية  الشعبية التي كان ،أو ما زال يمارسها الآباء ،والأجداد ،وكما استخدمت المقابلة المباشرة مع أرباب الصناعات، والحرف الشعبية، والشعراء الشعبيين. بعد هذا العرض ،والإجابة على أسئلة الدراسة ،وعليه يمكن الإشارة إلى النتائج الآتية: 1-الربابة من الأدوات الموسيقية الشعبية التراثية ، ،والتقليدية ذات بعد عائلي، وأسري، وتنتشر في مناطق ذات الطابع البدوي-منطقة الجنوب الفلسطيني –من بيت لحم ،الخليل،بئر السبع والنقب ،وغزة. 2-تعمل على تلبية احتياجات الشاعر الشعبي بطرق فنية مبتكرة، بأشكال وأحجام متنوعة خاصة للإغاثة وطلب النجدة والمساعدة. 3- موادها الأولية، والمواد الخام متوافرة في البيئة المحلية. 4-مستقبل الربابة في انقراض لأن العازفين من جيل الآباء والأجداد ولا يتعلمها الشباب. 5-الربابة آلة موسيقية نسيها الزمن. 6-الربابة استعملها الشعراء في مجالس السهر والمضافات والدواوين والتعاليل والسهرات للتفريغ النفسي ببث الهموم والمشاكل والآهات والحسرة والألم وهي رفيقة درب البدوي في الحل والترحال  وكان يعلقها على عمود وسط البيت-العامر-بجانب السف –لعلو منزلتها وقيمتها عنده. 7-الربابة هي الأب الروحي للأدوات والآلات الموسيقية وتطورت عنها الكمنجة والبزق. 8-العلاقة العضوية مع الشعر العربي والسير الشعبية-مصاحبة حسية. 9-أضاف عليها الشعار الشعبي زخرفة ونقوش ورسومات للتباهي . 10-إيقاع الربابة يخرج بتمازج صوت الشعار الشعبي مع وتر الربابة-سبيب الشعر-.   abstract Musical instrument popular forgotten time Rababa sad chord of popular musical instruments And its role in enriching the art scene in Palestine Prepared by D.Edrees  Mohammed Saqr Jaradat Sanabel Center for Studies and Folklore - Sa'ir - Mobile 0599206664 Email sanabelssc1@yahoo.com Summary      The study sought to achieve the following To work on the revival of an important aspect of Palestinian heritage, a popular musical instruments, and traditional crafts for their development, and conservation Highlight the dimensions heritage and civilization of the popular industries that reflect the history of the Palestinian people and its culture, which embodies the Palestinian presence on the land        The study followed a descriptive approach, which runs according to the following steps: descriptive side of the reality of popular musical instruments - rababa with sad chord - and desktop approach with reference to books, magazines, and books about extinct private industries.          The study used unintended observation direct, so as to collect experiences on what we see, or hear about, so as to get to know the reality of musical instruments popular that it was, or is still practiced by parents, grandparents, and also used the interview directly with employers industries, folk crafts, and poets . After answering the questions of the study, it can be referred to the following results: Rababa the popular musical instruments, heritage, traditional family, and spread in areas with a Bedouin character - the South - Palestinian from Bethlehem, Hebron, Beersheba , the Negev, and the Gaza Strip Working to meet the needs of the popular poet technical innovative ways, in a variety of shapes and sizes private relief and asked for help and assistance - Raw materials, raw materials available in the local environment.3 Future rababa is in extinction because of instrumentalists generation of parents and grandparents taught to young people Rababa is the forgotten musical instrument .. Rababa used by the poets on the boards ensure additives and divans and Altaaleil and evening for unloading psychological broadcast worries and problems and groans and anguish and pain is a fellow trail Bedouin in the solution and travel and was attached to the column, the center of the house Rababa of the spiritual father of the tools, musical instruments and developed by violin and bouzouki Organic relationship with poetry and popular Sir - sensory accompany.8 Added by popular ornament logo and inscriptions and drawings to show off Rhythm rababa is like the voice of the popular slogan with water . In light of the findings of the study, the Committee recommends the following The recommendations of the research and academic institutions to conduct research and studies proposed future descriptive studies, and analytical data fact, facts, through systems analysis method input - processes - outputs comparative studies with practical experience to revive the folklore, and traditional industries in the Arab countries, and foreign Activating the role of research centers in the Palestinian universities, faculty, under the guidance of university students in different colleges, research work, and graduation projects in Palestinian folklore. Recommendations for human rights and humanitarian organizations and local community institutions - raise awareness of the poets and folk music in Palestinian society.1 - to intensify work on media programs in radio stations, local television.2 – 3. hold workshops specializing in Palestinian folklore, and his defense mechanism, and protect it from obliteration and extinction Recommendations for government ministries: labor, economy and trade, culture, education, and endowments and the media, and the Palestinian tourism popular support industries, and traditional crafts and funded financially, through the establishment of a special fund for this, overseen by the relevant ministries, such as tourism, culture, trade, industry, and education – 2. Organizing workshops and training to the owners of traditional crafts, to technological improvements – 3.Seminars, study days, to educate the next generation, and young people, the importance of traditional industries, and promote interest in them - 4. develop an educational program for the development of people's perceptions of the importance of heritage, and the positive impact that afford these industries on the environment, the tourism sector, and the preservation of national identity